Biosimilar Insulins Are Coming: The Top 10 Things you Should Know. Issue 3 (May 2014) - Blumer, Ian; Edelman, Steven
Abstract : : Biologic drugs, such as currently prescribed insulins, are large, complex, 3-dimensional molecules manufactured in biological systems. The complexity of the structure of the biologic drug and its manufacturing process means that it is challenging to create a biologic drug that is identical to the original branded drug. With the potential availability on the horizon of follow-on insulin products (also known as biosimilar insulins) in the United States and other countries where they are not currently in use, physicians (and other prescribers) need to be aware of the potential benefits and concerns regarding biosimilar insulins in order to facilitate informed decision making and to provide the best possible advice and guidance to their patients with diabetes. This article offers a brief, practical overview regarding biosimilar insulins by answering 10 key questions about the topic.